Freezing-Tolerant Supramolecular Adhesives from Tannic Acid-Based Low-Transition-Temperature Mixtures - Mercadal, Pablo A.; Montesinos, María del Mar; Macchione, Micaela A.; Dalosto, Sergio D.; Bierbrauer, Karina L.; Calderón, Marcelo; González, Agustín; Picchio, Matías L. (2024)
2 Year Impact Factor 2023: 9.6